2018 European Thyroid Association (ETA) Guidelines for the Management of Amiodarone-Associated Thyroid Dysfunction. Issue 2 (14th March 2018) - Bartalena, Luigi; Bogazzi, Fausto; Chiovato, Luca; Hubalewska-Dydejczyk, Alicja; Links, Thera P.; Vanderpump, Mark
Abstract : Treatment with amiodarone is associated with changes in thyroid function tests, but also with thyroid dysfunction (amiodarone-induced hypothyroidism, AIH, and amiodarone-induced thyrotoxicosis, AIT). Both AIH and AIT may develop in apparently normal thyroid glands or in the presence of underlying thyroid abnormalities. AIH does not require amiodarone withdrawal, and is treated with levothyroxine replacement if overt, whereas subclinical forms may be followed without treatment. Two main types of AIT are recognized: type 1 AIT (AIT 1), a form of iodine-induced hyperthyroidism occurring in nodular goitres or latent Graves disease, and type 2 AIT (AIT 2), resulting from destructive thyroiditis in a normal thyroid gland. Mixed/indefinite forms exist due to both pathogenic mechanisms. AIT 1 is best treated with thionamides that may be combined for a few weeks with sodium perchlorate to make the thyroid gland more sensitive to thionamides. AIT 2 is treated with oral glucocorticoids. Once euthyroidism has been restored, AIT 2 patients are followed up without treatment, whereas AIT 1 patients should be treated with thyroidectomy or radioiodine. Mixed/indefinite forms of AIT are treated with thionamides. Oral glucocorticoids can be added from the beginning if a precise diagnosis is uncertain, or after a few weeks if response to thionamides alone is poor. The decision to continue or to stop amiodarone in AIT should be individualized in relation to cardiovascular risk stratification and taken jointly by specialist cardiologists and endocrinologists. In the presence of rapidly deteriorating cardiac conditions, emergency thyroidectomy may be required for all forms of AIT.